2021
DOI: 10.1038/s43018-021-00254-0
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory CSF2-driven macrophage activation promotes adaptive resistance to CSF1R inhibition in breast-to-brain metastasis

Abstract: Tumor microenvironment-targeted therapies are emerging as promising treatment options for different cancer types. Tumor-associated macrophages and microglia (TAMs) represent an abundant non-malignant cell type in brain metastases and have been proposed to modulate metastatic colonization and outgrowth. We used an inhibitor of colony stimulating factor 1 receptor (CSF1R) to target TAMs at distinct stages of the metastatic cascade in preclinical breast-to-brain metastasis models and found that CSF1R inhibition l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 86 publications
3
30
0
Order By: Relevance
“…42 Importantly, a recent study reported, in a mouse model of breast-to-brain metastasis, that the inhibition of CD115 induced a compensatory increase of GM-CSF synthesis by pericytes that induced the acquisition by TAM of an inflammatory and tissue repair profile. 49 One can thus suspect that, in vivo, the neutralization of the M-CSF-IL-34/CD115 axis may exacerbate the role of GM-CSF, which would then promote the generation, in humans, of inflammatory macrophages favoring tumor recurrence.…”
Section: Differences In the Processes Of Generation And Functional Po...mentioning
confidence: 99%
“…42 Importantly, a recent study reported, in a mouse model of breast-to-brain metastasis, that the inhibition of CD115 induced a compensatory increase of GM-CSF synthesis by pericytes that induced the acquisition by TAM of an inflammatory and tissue repair profile. 49 One can thus suspect that, in vivo, the neutralization of the M-CSF-IL-34/CD115 axis may exacerbate the role of GM-CSF, which would then promote the generation, in humans, of inflammatory macrophages favoring tumor recurrence.…”
Section: Differences In the Processes Of Generation And Functional Po...mentioning
confidence: 99%
“…In contrast to previous findings from glioblastoma mouse models, where TAMs survived CSF1R inhibition and were instead re-educated ( 169 , 170 ), a recent work demonstrated that targeting TAMs with the CSF1R inhibitor BLZ945 delayed brain metastatic onset and led to an initial tumor response with transient stasis of established metastases ( 232 ).CSF1R inhibitors have also been evaluated in combination treatments in preclinical studies. In breast cancer models, the efficacy of paclitaxel (Taxol) was enhanced by CSF1R inhibitor–mediated TAM depletion ( 10 , 233 ).…”
Section: Macrophagesmentioning
confidence: 89%
“…With regard to this result, an inhibitor of STAT5, AC4-130, was added to BLZ945 and led to significant synergistic anti-tumor effects with reduced tumor growth. Moreover, the combination induced a morphological change of TAM and reduced neuro-inflammation [ 90 ]. Previously, we discussed the key role of G-CSF in the maturation and recruitment of proinflammatory neutrophils in BM.…”
Section: Targeting Cytokines For Treatmentmentioning
confidence: 99%